2017
DOI: 10.1371/journal.pone.0182026
|View full text |Cite
|
Sign up to set email alerts
|

The role of physique, strength and endurance in the achievements of elite climbers

Abstract: PurposeThe primary aim of this study is to determine the principal somatic and motor determinants for elite climbers.MethodsTwenty climbers were examined [age: 28.5±6.1 years].The runners were divided into two groups based on their climbing level, according to the International Rock Climbing Research Association (IRCRA). Elite climbers represented a 8b-8c Rotpunkt (RP) climbing level (n = 6), and advanced climbers represented an 7c+-8a RP level (n = 14). The following measurements were assessed: height, weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 14 publications
(29 reference statements)
1
33
2
1
Order By: Relevance
“…This finding is in line with previous studies on chronic injuries in climbing 7. But this is in contrast with the findings of Lion et al 5. Lion et al suggest that there is an association between finger injuries and BMI.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…This finding is in line with previous studies on chronic injuries in climbing 7. But this is in contrast with the findings of Lion et al 5. Lion et al suggest that there is an association between finger injuries and BMI.…”
Section: Discussioncontrasting
confidence: 60%
“…In sports, comparable to climbing in terms of criteria for success and anthropometrics like gymnastics running and ski jumping, the body mass index (BMI) is linked to performance2 3 and injuries 4. During a climbing performance the load on the fingers, elbow and shoulders is shown to be substantial 5. Furthermore, the physiological load increases with an increase in BMI; a lower BMI will give a lower load and thereby, apparently, reduce the odds for injury.…”
mentioning
confidence: 99%
“…To date, research has identified four major fitness benefits from climbing: muscular strength and endurance, flexibility and aerobic fitness [11,16,23]. While positive effects were generally found in grip and upper body strength [16,20,23], this study has identified positive impact on ankle dorsiflexion strength and ankle DF-ROM. This is interesting as ankle dorsiflexion function has been found to be a relevant physiological limitation in pediatric oncology presumably resulting in impaired mobility and gait [2].…”
Section: Discussionmentioning
confidence: 68%
“…However, it should be noted that average heart rates of 114-150 bpm were documented and the maximum heart rate reached up to 250 bpm. While indoor wall climbing has previously been found to be a moderate to vigorous type of PA [8,21] it should be discussed whether a climbing session must even be considered a high intensity interval training (HIT), as it involves short intermittent high intensity climbing activity with numerous isometric muscle contractions and longer periods of rest in between [20,21]. Moreover, it needs to be noted that several studies found a disproportional rise in heart rate compared to VO 2 during climbing potentially due to i. e. the isometric handgrip exercise causing disproportional rise in blood pressure, the arm position mainly above the level of the heart or psychological stress or anxiety [22].…”
Section: Discussionmentioning
confidence: 99%
“…The significant effect of fitness-related abilities on the level of achievement of climbers has been emphasized by numerous researchers [1,[6][7][8]. The major determinants of success in climbing include finger and arm strength, muscle endurance [1,7,9], specific hip mobility [10], and characteristics of body build, such as low body mass, low body fat, and average body height [9,11,12]. Flexibility has been identified as one of four abilities that determine success in climbing [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%